The future of interlinked, interoperable and scalable metadata. (2nd July 2020) - Alemu, Getaneh; Garoufallou, Emmanouel
With the growing diversity of information resources the emphasis on data-centric applications such as big data, metadata, semantics and ontologies has become central. This editorial paper presents a summary of recent developments in metadata, semantics and ontologies - focusing in particular on metadata enriching, linking and interoperability. National libraries and archives are devising new bibliographic models and metadata presentation formats. Bibliographic metadata sets are being made available using these new data formats such as RDF. The new formats are aiming to represent data in granular structures and define unique identification protocols such as URIs. The paper concludes by introducing the five papers included in the special issue. The papers in this special issue present novel approaches to metadata integration, interoperability frameworks, re-use of metadata ontologies and methods of metadata quality analysis.